Fall Prevention: Who's at Risk? - Sergio Romero (EDIS)
There are many risk factors associated with falls. Some risks are environmental, like poor lighting. Others relate to diseases people have or medications they take. It’s important to know if you are at high risk of falling. Take this quiz in this document to see if you are at risk. This document is FCS2227, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: April 2005.